Evaluation of the gastronomy tourism potential of Beykoz district by SWOT analysis - Teyin, Görkem (2024)
In this study, in order to determine the gastronomy tourism potential of Beykoz district, located in the province of Istanbul, it was aimed to determine the strengths-weaknesses and opportunities-threats of the district in terms of gastronomy tourism by SWOT analysis. While the population of the study consists of tourism businesses operating in the Beykoz district of Istanbul, the sample of the study consists of 28 business managers and enterprises who voluntarily participated in the study among the tourism businesses operating in this district. In the study, interview technique, one of the qualitative data collection methods, was used and content analysis was applied to the obtained data. When the findings obtained as a result of the study are examined, it is seen that the strength of the district is its geographical location, its weakness is the lack of promotion, advertising and socio-cultural structure, its biggest opportunity is that it has coasts to the Marmara and Black Sea and is located on the Bosphorus, and its threats are that investors in the region have not been able to adopt the concept of gastronomy tourism. For future studies, research can be done based on the SWOT data obtained from the study, and studies are recommended especially for local, indigenous products and products with regional geographical indication potential. It is thought that as the number of such studies increases, an element of attraction can be created in the region and a destination image can be created.